2018
DOI: 10.1124/jpet.117.244756
|View full text |Cite
|
Sign up to set email alerts
|

Soy Phosphatidylglycerol Reduces Inflammation in a Contact Irritant Ear Edema Mouse Model In Vivo

Abstract: We have previously shown that phosphatidylglycerol (PG) regulates the function of keratinocytes, the predominant cells that compose the epidermis, inhibiting the proliferation of rapidly dividing keratinocytes. In particular, soy PG, a PG mixture with a high proportion of polyunsaturated fatty acids, is efficacious at inhibiting these proliferating keratinocytes. Psoriasis is a skin disorder characterized by hyperproliferation of keratinocytes and inflammation. Data in the lung suggest that PG in pulmonary sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…This result suggests that PG may be an effective therapeutic for treating sterile inflammation, that is, inflammation resulting from noninfectious causes, such as occurs in skin diseases but also in corneal disorders such as chemical burns and dry eye syndrome and in stroke, neurodegenerative diseases, myocardial infarction, and atherosclerosis (Oh et al, 2012). In this regard, we suggest that inhibition of DAMPinduced inflammation may explain the previously observed ability of PG to decrease skin inflammation in response to the contact irritant 12-O-tetradecanoylphorbol 13-acetate (Xie et al, 2018). 12-O-tetradecanoylphorbol 13-acetate is known to up-regulate antimicrobial peptides like S100A8 and S100A9 (Gebhardt et al, 2002;McNeill and Hogg, 2014); therefore, we hypothesize that PG inhibits 12-O-tetradecanoylphorbol 13-acetateeinduced inflammation in this model in part by blocking inflammatory mediator production elicited by 12-O-tetradecanoylphorbol 13-acetateeincreased antimicrobial peptides.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This result suggests that PG may be an effective therapeutic for treating sterile inflammation, that is, inflammation resulting from noninfectious causes, such as occurs in skin diseases but also in corneal disorders such as chemical burns and dry eye syndrome and in stroke, neurodegenerative diseases, myocardial infarction, and atherosclerosis (Oh et al, 2012). In this regard, we suggest that inhibition of DAMPinduced inflammation may explain the previously observed ability of PG to decrease skin inflammation in response to the contact irritant 12-O-tetradecanoylphorbol 13-acetate (Xie et al, 2018). 12-O-tetradecanoylphorbol 13-acetate is known to up-regulate antimicrobial peptides like S100A8 and S100A9 (Gebhardt et al, 2002;McNeill and Hogg, 2014); therefore, we hypothesize that PG inhibits 12-O-tetradecanoylphorbol 13-acetateeinduced inflammation in this model in part by blocking inflammatory mediator production elicited by 12-O-tetradecanoylphorbol 13-acetateeincreased antimicrobial peptides.…”
Section: Discussionmentioning
confidence: 71%
“…However, another characteristic of psoriasis is (sterile) inflammation with extensive immune cell infiltration into the skin. Although we have previously shown that PG derived from soy is able to suppress these parameters in a contact irritant ear edema mouse model (Xie et al, 2018), the mechanism by which PG affects skin inflammation remains unknown.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, PG species binding polyunsaturated fatty acids (PUFAs) such as linoleic acid (LA, 18:2n‐6) were found to be effective at inhibiting keratinocyte proliferation, whereas PG species possessing saturated or monounsaturated fatty acids promoted proliferation in slowly dividing keratinocytes . The current study indicated that, soybean PG which mainly contains linoleic acid suppressed inflammation in mouse contact irritant mouse ear edema models . These results suggested that molecular species of PG containing specific fatty acids may regulate keratinocyte growth and inflammation associated with skin diseases.…”
Section: Introductionmentioning
confidence: 60%
“…Soy PG possesses a large percentage of polyunsaturated fatty acids, with particular efficacy to inhibit keratinocyte proliferation (Xie et al, 2014), suggesting that it might be used to suppress the keratinocyte hyperproliferation characteristic of psoriasis. Indeed, we showed that soy PG inhibits inflammation and mouse ear swelling induced by the contact irritant 12-O-tetradecanoylphorbol 13-acetate in vivo (Xie et al, 2018). However, the mechanism by which soy PG functions to suppress inflammation is unclear.…”
Section: Introductionmentioning
confidence: 96%